Recognising oneself as educator. Findings from a case study conducted in the internship training for Social Education Bachelor's Degree. - Martos-Pérez, Maria-Victoria; Caparrós-Martín, Ester; Blanco-García, Nieves (My University, 2023)
In this paper I share the results of the analysis of a case study of a Social Education student through a qualitative enquiry with a narrative approach (Clandinin and Connelly, 1994, 2000; Van Manen, 2003, 1990). It delves into her experience and formative trajectory within the Practicum course of the Bachelor's Degree in Social Education at the University of Malaga (Spain); a course that took place during three consecutive years, oriented to the realisation of training practices in profesional contexts. The focus of this study, which is part of a larger thesis project, is to approach the development of professional knowledge in the initial training of social educators in the context of this subject. Being a social educator requires more than just knowing what to do and how to do it. Social education professionals develop their profession in situations and problems that cannot be solved by applying knowledge, but by developing practical knowledge that allows them to make situational judgements about what is appropriate and desirable (Biesta, 2013, 2017) at each moment and with each person. Initial training plays an important role in the development of professional identity and critical thinking that allows students to construct their own knowledge, which is indispensable for the educational profession exercise: determining who they want to be and how they want to do their profession. That is, learning to act on the basis of who they are, becoming aware of their own pedagogical being and taking responsibility for their actions (Blanco and Sierra, 2013). In this sense, this context of theoretical-practical and professional training is one of the most important and highly valued subjects within the Degree in Social Education, mainly due to its proximity to professional practice. During these practical periods, students attend socioeducational centres attached to the university, for several days a week, and are accompanied by an academic tutor.
Keywords: Investigación activa en educación; Grado en Educación Social - Estudio y enseñanza; Socialisation; Social education; Case study; Narrative inquiry; Training practices